Sonatine: Op.36 - CLEMENTI, M (Universal edition)
Buku ini terdiri dari: sonatine op.36.no 1, sonatine op.36.no 2, sonatine op.36.no 3, sonatine op.36.no 4, sonatine op.37.no 1, sonatine op.37.no 2, sonatine op.37.no 3, sonatine op.38.no 1, sonatine op.38. no 2, sonatine op.38. no 3